Epidemiological evidences on overdiagnosis of prostate and kidney cancers in Korean - Bae, Jong-Myon (Epidemiol Health, 2015)
OBJECTIVES: The prostate specific antigen test is widely used as the main method of screening prostate cancer in Korea. Additionally, the use of ultrasound sonography may lead to overdiagnosis of kidney cancer as well as thyroid cancer. This study aimed to highlight epidemiological evidences regarding overdiagnosis of prostate and kidney cancers in Korean. METHODS: The annual trends of national incidence and mortality of prostate and kidney cancers provided by the Korean Statistical Information Service were evaluated. RESULTS: The rate of increase in the incidence of prostate and kidney cancer was 6 and 5 times higher than that of mortality between 2000 and 2011, respectively. Additionally, the age group showing the highest incidence in prostate cancer shifted from 85 years and older to 75-79 years. CONCLUSIONS: This evidence suggests that prostate and kidney cancers are overdiagnosed in Korea. Further research in this area, using national cancer registry databases, should be encouraged to prevent overdiagnosis.